Hybrid specification of reactive systems: An institutional approach - Madeira, A.
This paper introduces a rigorous methodology for requirements specification of systems that react to external stimulus by evolving through different operational modes. In each mode different functionalities are provided. Starting from a classical state-machine specification, the envisaged methodology interprets each state as a different mode of operation endowed with an algebraic specification of the corresponding functionality. Specifications are given in an expressive variant of hybrid logic which is, at a later stage, translated into first-order logic to bring into scene suitable tool support. The paper's main contribution is to provide rigorous foundations for the method, framing specification logics as institutions and the translation process as a comorphism between them. © 2011 Springer-Verlag.